2022
DOI: 10.1101/2022.04.20.488969
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intrinsic furin-mediated cleavability of the spike S1/S2 site from SARS-CoV-2 variant B.1.1.529 (Omicron)

Abstract: The ability of SARS-CoV-2 to be primed for viral entry by the host cell protease furin has become one of the most investigated of the numerous transmission and pathogenicity features of the virus. Here, we analyzed the S1/S2 cleavage site (also called “furin cleavage site”) of the spike protein of SARS-CoV-2 B.1.529 (Omicron variant) in vitro, to assess the role of two key mutations (spike gene, N679K and P681H) compared to the ancestral B.1 virus. We observed significantly increased intrinsic cleavability wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 41 publications
2
35
0
1
Order By: Relevance
“…This is contrary to several previous reports 19,23 , but in line with a recent report from Mesner et al 40 . This also correlates with single amino acids changes adjacent to the FCS in Omicron - specifically N679K and P681H - that on their own enhance cleavage 41 (Extended data figure 5C,D). Substitutions in S2 including residue 969 did not impact spike FCS cleavage (Figure 4E).…”
Section: Resultsmentioning
confidence: 60%
“…This is contrary to several previous reports 19,23 , but in line with a recent report from Mesner et al 40 . This also correlates with single amino acids changes adjacent to the FCS in Omicron - specifically N679K and P681H - that on their own enhance cleavage 41 (Extended data figure 5C,D). Substitutions in S2 including residue 969 did not impact spike FCS cleavage (Figure 4E).…”
Section: Resultsmentioning
confidence: 60%
“…These results reflect computational and experimental reports that state that the P681H and P681R mutations increase affinity to and cleavage capacity by furin. [34][35][36][37] No significant differences were found between the predicted scores and number of residue 681-interacting residues for ensemble docking of the Wild-type, Alpha, Delta, and Omicron S1/S2 sites to TMPRSS2 (Supporting Information: Table 2). Although the affinities did not significantly differ when comparing furin and TMPRSS2 dockings to one another, less poses were reported for docking of the all spike variant S1/S2 site conformers to TMPRSS2, which was interpreted as having less structural complementary and, thus, affinity to the S1/S2 cleavage sites.…”
Section: Ensemble Docking Of Spike Protein S1/s2 Site To Host Proteasesmentioning
confidence: 99%
“…This increase in the number of positive charges is crucial for the host protease in order to cleave the S-protein. However, several experimental studies have found that the Omicron S-protein cleaves less efficiently than other VOCs [12, 30–32], while another study has indicated the opposite [29]. This contradiction indicates that increased PC in Omicron may have other consequences, not yet elucidated.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, Omicron bears two more mutations close to this site, H655Y and N679K, which are likely to impact its S-protein cleavability by adding more positive charges to this site, but there are many debates about this prediction. Some studies have found that Omicron S-protein cleaves to be less effective than other variants [12,[30][31][32], while others revealed the opposite view that the presence of the N679K with P681H mutations in Omicron significantly increases furin-mediated S1/S2 cleavability [29].…”
Section: Role Of Cleavage Sites In Viral Transmission Of Omicron Variantmentioning
confidence: 99%
See 1 more Smart Citation